Barriers and Facilitators to Delivering Multifactorial Risk Assessment and Communication for Personalized Breast Cancer Screening: A Qualitative Study Exploring Implementation in Canada - Meghan J. Walker; Anna Neely; Antonis C. Antoniou; Mireille J. M. Broeders; Jennifer D. Brooks; Tim Carver; Jocelyne Chiquette; Douglas F. Easton; Andrea Eisen; Laurence Eloy; D. Gareth R. Evans; Samantha Fienberg; et al. (Current Oncology)
Many jurisdictions are considering a shift to risk-stratified breast cancer screening; however, evidence on the feasibility of implementing it on a population scale is needed. We conducted a prospective cohort study in the PERSPECTIVE I&I project to produce evidence on risk-stratified breast screening and recruited 3753 participants to undergo multifactorial risk assessment from 2019–2021. This qualitative study explored the perspectives of study personnel on barriers and facilitators to delivering multifactorial risk assessment and risk communication. One focus group and three one-on-one interviews were conducted and a thematic analysis conducted which identified five themes: (1) barriers and facilitators to recruitment for multifactorial risk assessment, (2) barriers and facilitators to completion of the risk factor questionnaire, (3) additional resources required to implement multifactorial risk assessment, (4) the need for a person-centered approach, and (5) and risk literacy. While risk assessment and communication processes were successful overall, key barriers were identified including challenges with collecting comprehensive breast cancer risk factor information and limited resources to execute data collection and risk communication activities on a large scale. Risk assessment and communication processes will need to be optimized for large-scale implementation to ensure they are efficient but robust and person-centered.